Biofeedback Prototype System for Stress Level Assessment during a Driving Simulation Session (LACCEI, 2024)
Urban traffic congestion has become a factor that generates stress, mainly in people who drive daily. For road safety reasons, it is crucial to identify whether driving a vehicle increases the driver's stress level because this could affect their health or decision-making. This research seeks to determine whether driving (in a simulation environment) alters the stress level of people. Therefore, a biofeedback system prototype is designed and built based on heart rate sensors, body temperature, and brain activity to measure the increase and decrease of these parameters. Considering that each person responds differently to stimuli, the experimental procedure applied the questionnaire to DASS-21 and binaural music to analyze the participants' stress levels before the experiment. The data collected were reviewed by a physician to ensure the sensitivity of the sensors to the physiological parameters, reaching 92% reliability.